Transición de NIC 11; 18 a NIIF 15 y su impacto en la utilidad, Contructec Vel Servicios Generales SAC, 2018 - Castillo Rios, Jose Angel Michel (2021)
This research work was carried out in order to determine the impact on profit, as a result of the transition from IAS 11 and IAS 18 to IFRS 15 in the financial statements of the company, Contructec Vel Servicios Generales SAC. This research used the analytical and descriptive method for which bibliographic references, table elaboration, among others were used; in order to test the proposed hypothesis and with a non-experimental design because there is no manipulation of the variables. The sample is defined by 8 people from the accounting area, where the survey was used as a technique for collecting information on the financial statements of the company, as well as the documentary analysis and the respective bibliographic research to support the information found in this research. It is concluded that the income from ordinary activities comes from contracts with clients significantly affect the utility of the company, contrasting the research hypothesis using Spearman statistical test. Finally, it was recommended to the senior management of the company to train the accounting department on the application of this standard and to consider the accounting guidelines, according to the case of work or service that is presented to obtain better results when carrying out its application, also the company carry out a precise study of its scope, in order to make sure that the standard can be applied without inconvenience at the time of its implementation.